Chemerin, a novel adipokine in the regulation of angiogenesis - Bozaoglu, K.; Curran, J.; Stocker, C.; Zaibi, M.; Segal, D.; Konstantopoulos, N.; Morrison, S.; Carless, M.; Dyer, T.; Cole, S.; Goring, H.; Moses, Eric; et al. (The Endocrine Society, 2010)
Context: Chemerin is a new adipokine associated with obesity and the metabolic syndrome. Gene expression levels of chemerin were elevated in the adipose depots of obese compared with lean animals and was markedly elevated during differentiation of fibroblasts into mature adipocytes. Objective: The objective of the studywasto identify factors that affect the regulation and potential function of chemerin using a genetics approach. Design, Setting, Patients, and Intervention: Plasma chemerin levels were measured in subjects from the San Antonio Family Heart Study, a large family-based genetic epidemiological study including 1354 Mexican-American individuals. Individuals were randomly sampled without regard to phenotype or disease status. Main Outcome Measures: A genome-wide association analysis using 542,944 single-nucleotide polymorphisms in a subset of 523 of the same subjects was undertaken. The effect of chemerin on angiogenesis was measured using human endothelial cells and interstitial cells in coculture in a specially formulated medium. Results: Serum chemerin levels were found to be highly heritable (h 2 = 0.25; P = 1.4 × 10-9). The single-nucleotide polymorphism showing strongest evidence of association (rs347344; P = 1.4 × 10-6) was located within the gene encoding epithelial growth factor-like repeats and discoidin I-like domains 3, which has a known role in angiogenesis. Functional angiogenesis assays in human endothelial cells confirmed that chemerin significantly mediated the formation of blood vessels to a similar extent as vascular endothelial growth factor. Conclusion: Here we demonstrate for the first time that plasma chemerin levels are significantly heritable and identified a novel role for chemerin as a stimulator of angiogenesis. Copyright © 2010 by The Endocrine Society.